A Comparative Review of Ancillary Service Markets: Benchmarking Global Practices and Implications for Indonesia - Indri Haryani; Valensi Erza; Hendri Bhirowo (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2026)
The rapid integration of renewable energy sources is transforming power system operations, resulting in reduced system inertia and increased operational variability. These modifications increase the demand for advanced ancillary service (AS) to ensure system stability, including frequency regulation, reserve provision, and voltage management. Unlike countries that have implemented market-based ancillary services and advanced technologies, Indonesia still operates ancillary services through centralized mechanisms with limited participation of new technologies. This report presents a comparative analysis of the development of ancillary service in selected countries by assessing aspects of market structure, pricing mechanisms, technology integration, regulatory frameworks, and operational maturity. A qualitative maturity assessment methodology is used to evaluate the level of implementation across various power systems. The findings reveal significant differences between developed and developing systems. Countries such as Australia, the United Kingdom, and the United States demonstrate more advanced maturity by incorporating rapid response technologies, competitive market frameworks, and real-time system operations. In contrast, Indonesia is still at an early stage with centralized management, limited technology integration, and the absence of a structured ancillary service market. Unlike existing comparative studies focused on OECD contexts, this paper explicitly targets the policy and implementation gap for a large, archipelagic, state utility dominated emerging economy. A five phase implementation roadmap is proposed for 2025–2034, aligned with RUPTL targets and calibrated to Indonesian institutional realities.